Acute Lupus Pneumotitis as a Complication of Pregnancy: A Case Report - I Gede Agus Rio Saputra; I Putu Bagus Darma Putra; I Wayan Artana Putra (Newinera Publisher, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease that is chronic in nature and has considerable clinical heterogeneity. Acute Lupus Pneumonitis (ALP) is one of its many presentations. We report the case of a 29-year-old, primigravida patient at 30 weeks of gestation presenting with progressive dyspnoea, phlegmatic cough lasting three weeks and morning fever. On physical examination, there was a stabilized alert patient with normal vital signs. Examination by auscultation of thorax revealed slight subcostal retraction and other rhonchi and wheezing. Cephalic foetal presentation was present in the abdomen and abdominal ultrasound was reported normal. Investigations in the laboratory showed thrombocytopenia, over iron-deficiency anaemia, and systemic inflammatory factors. The presence of demonstrable anti-SSA and anti-SSB antibodies provided support to the diagnosis of pregnancy-related suspicious SLE bronchopneumonia. A restrictive diet was established, which included ceftriaxone once per day, Methylprednisolone between two times per day, Nebulised salbutamol between three times per day, N-Acetyl cysteine between three times per day, hydroquinone once per day, aspartilet once a day, and vitamin D once a day. The patient was discharged four days after therapy after clinical improvement was noted. After two months, she gave birth to clinically healthy infant via caesarean section, due to breech presentation and placenta previa as well as the persistence of SLE with the risk of lupus flare. ALP is a dangerous pulmonary SLE process. Here, the positive anti-SSA and anti-SSB were especially worrying considering that such antibodies are linked to very severe maternal and foetal complications.